IDENTIFIKASI MANFAAT BISNIS TEKNOLOGI INFORMASI PADA PEMERINTAH DAERAH: STUDI KASUS PROVINSI SULAWESI UTARA - Wowor, Hans; Karouw, Stanley (Jurnal Teknik Informatika, 2013)
North Sulawesi province is fostering regional development towards a society which have values, prosperous and competitive cultures. Information Technology (IT) have become a key enabler to accelerate region developments. To optimize IT utilization, local government using IT Blueprint as a general guidelines for conduct IT investing. This paper will show that by using Ranti’s IS/IT Generic Business Value, all IT Business Value can be quantified in reasonable and responsible manner. This paper also proposed complete list for IT Business Value Specified for Local Governments.Keywords: IT Investment, IT Business Value, Local Government